2013
DOI: 10.4236/jbise.2013.66078
|View full text |Cite
|
Sign up to set email alerts
|

Systematic analysis of diabetes- and glucose metabolism-related proteins and its application to Alzheimer’s disease

Abstract: Alzheimer disease has been defined as Type 3 Diabetes due to their shared metabolic profiles. Like our previously research, results of Alzheimer's disease and other neurodegenerative diseases, systematic analysis of diabetes-and glucose metabolism-related proteins also provides help in the treatment of Alzheimer's patients. Some interesting results indicate that diabetes-related proteins (DRPs) are rich in Lys and the content of Trp can distinguish between type 1 and type 2 diabetes mellitus in particular, whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 106 publications
(161 reference statements)
0
7
0
Order By: Relevance
“…Previous work has indicated that single nucleotide polymorphisms for the PTPRN gene were differentially related to CSF p-tau levels in an MCI-AD converter group compared to an MCI nonconverter group [ 69 ]. To our knowledge, this is the first report that PTPRN levels are depressed in the CSF of AD patients and, given PTPRN’s role in metabolism [ 70 ], may open vistas to further examine metabolic theories of the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Previous work has indicated that single nucleotide polymorphisms for the PTPRN gene were differentially related to CSF p-tau levels in an MCI-AD converter group compared to an MCI nonconverter group [ 69 ]. To our knowledge, this is the first report that PTPRN levels are depressed in the CSF of AD patients and, given PTPRN’s role in metabolism [ 70 ], may open vistas to further examine metabolic theories of the development of AD.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also provided evidence about indirect genetic effects on certain chemical compounds or protein translocation, which are reflected in the PET scans and may be associated with AD. For example, Dai et al (2013) and Sakamoto & Holman (2008) demonstrated that TBC1D4 plays a role in the regulation of GluT4 traffic, which on the other hand is associated with AD (Talbot et al 2012; Yang, Li & Liu 2013). Nolte et al (2006) and Lu, He & Zhong (2007) have reported a chain of relationships of the HOXD4 gene to PAX6 protein in AD.…”
Section: Resultsmentioning
confidence: 99%
“…Our findings also provided evidence about indirect genetic effects on certain chemical compounds or protein translocation, which are reflected in the PET scans and may be associated with AD. For example, Dai et al (2013) and Sakamoto & Holman (2008) demonstrated that TBC1D4 plays a role in regulation of GluT4 traffic, which, on the other hand is associated with AD (Talbot et al, 2012;Yang, Li, & Liu, 2013). Nolte et al (2006) and Lu, He, & Zhong (2007) have given a chain of relationships of HOXD4 gene to PAX6 protein to AD.…”
Section: Resultsmentioning
confidence: 99%